International assignments: factors influencing employee’s job performance while working abroad / Nurul Izzati Syazwan Mohamad Sakri - Mohamad Sakri, Nurul Izzati Syazwan (2015)
International crises experienced by multinational corporations include both the premature return of employees due to failed assignments and the poor job performance while working abroad. To reduce the direct and indirect costs relating to expatriate failure, multinational corporations are striving to improve their capability to manage their employee’s job performance before, during and after international assignments. This article highlights these issues and discusses the factors influencing employee’s job performance while working abroad. The results of the study presented in this paper suggest proper cross-cultural adjustment for employees, spouses and their family members and sufficient psychological support from home country are being acknowledged as major determinants of success or failure in international business. It concludes that by proposing both adjustments by giving appropriate trainings and psychological support may help to resolve the employee’s poor job performance while working abroad.